Correction: Facile synthesis of mesoporous spinel NiCo2O4 nanostructures as highly efficient electrocatalysts for urea electro-oxidation. Issue 21 (8th May 2015) - Ding, Rui; Qi, Li; Jia, Mingjun; Wang, Hongyu
Abstract : Correction for 'Facile synthesis of mesoporous spinel NiCo2 O4 nanostructures as highly efficient electrocatalysts for urea electro-oxidation' by Rui Ding et al., Nanoscale, 2014, 6, 1369–1376.